Does the Academy of Breastfeeding Medicine's Clinical Protocol #36 'The Mastitis Spectrum' promote overtreatment and risk worsened outcomes for breastfeeding families? Commentary - Pamela Douglas (BMC, 2023)
Abstract Background In 2022 the Academy of Breastfeeding Medicine (ABM) published Clinical Protocol #36: The Mastitis Spectrum, which aims to update clinical approaches to management of benign lactation-related breast inflammation. The protocol has been timely because of the exponential increase in knowledge about the human milk microbiome over the past decade. This Commentary aims to continue respectful debate amongst clinicians and researchers within the Academy of Breastfeeding Medicine and more broadly, confident that we share a fundamental commitment to promote breastfeeding and support the well-being of lactating women, their infants and their families. Analysis Although Clinical Protocol #36 offers advances, it does not fulfil the principles of best practice implementation science for translation of evidence into clinical guidelines. Clinical Protocol #36 inaccurately represents studies; misrepresents theoretical models as proven aetiologies; does not consistently attribute sources; does not reliably apply the SORT taxonomy; and relies upon single case reports. As a result, various recommendations in Clinical Protocol #36 lack an evidence-base or credible underlying theoretical model. This includes recommendations to use 'lymphatic drainage' massage, therapeutic ultrasound, and oral lecithin. Similarly, based on a contestable theoretical model which is presented as fact, Clinical Protocol #36 makes the recommendation to either reduce frequency of milk removal or to maintain current frequency of milk removal during an episode of breast inflammation. Although Clinical Protocol #36 limits this advice to cases of 'hyperlactation', the diagnosis 'hyperlactation' itself is undefinable. As a result, this recommendation may put breastfeeding women who present with breast inflammation at risk of worsened inflammation and decreased breast milk production. Conclusion Clinical Protocol #36 offers some advances in the management of breast inflammation. However, Clinical Protocol #36 also exposes clinicians to two international trends in healthcare which undermine health system sustainability: overdiagnosis, including by over-definition, which increases risk of overtreatment; and antibiotic over-use, which worsens the crisis of global antimicrobial resistance. Clinical Protocol #36 also recommends unnecessary or ineffective interventions which may be accessed by affluent patients within advanced economies but are difficult to access for the global majority. The Academy of Breastfeeding Medicine may benefit from a review of processes for development of Clinical Protocols.